ORGANIC FERTILIZERS AND THEIR PROPERTIES - Fozilova Munira Nasimiddin qizi; Berdiyeva Malika Azim qizi; Big’amova Farangiz Ziyadulla qizi (Scholar Express Journal, 2024)
This article provides analytical information on the characteristics of organic fertilizers and their effect on the regime of nutrients in the soil.
Keywords: Manure; compost; nitrogen; phosphorus